2022
DOI: 10.36941/jesr-2022-0084
|View full text |Cite
|
Sign up to set email alerts
|

Self-Determination of Persons with Sensory Disabilities

Abstract: This study aimed to determine female pre-service teachers’ attitudes toward self-determination skills for persons with sensory disabilities. Data were collected using a questionnaire of attitudes toward self-determination skills from 80 female pre-service teachers at Mu’tah University in Jordan to achieve the study’s aims. The findings indicated that their attitudes were positive. There were no statistically significant differences in teachers’ attitudes toward self-determination skills for persons with sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…These values are presented in Table 3. (Alhaddad et al, 2018;AlTarawneh & Etawi, 2022;Cohen, 2020;The Global Down Syndrome Foundation, 2023;Mohaidat & AlKatatbeh, 2021;National Down Syndrome Society, 2023;New South Wales, 2023;Pace et al, 2010;Santoro & Steffensen, 2021;Schools, 2019;Urbano & Hadapp, 2007). Overall, this finding of inadequate awareness in special education students aligns with the assumption that better treatment of the condition owing to medical advancements and increasingly inclusive social practices relating to people with Down syndrome have also functioned to perpetuate the paucity of knowledge and misunderstandings regarding Down syndrome.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are presented in Table 3. (Alhaddad et al, 2018;AlTarawneh & Etawi, 2022;Cohen, 2020;The Global Down Syndrome Foundation, 2023;Mohaidat & AlKatatbeh, 2021;National Down Syndrome Society, 2023;New South Wales, 2023;Pace et al, 2010;Santoro & Steffensen, 2021;Schools, 2019;Urbano & Hadapp, 2007). Overall, this finding of inadequate awareness in special education students aligns with the assumption that better treatment of the condition owing to medical advancements and increasingly inclusive social practices relating to people with Down syndrome have also functioned to perpetuate the paucity of knowledge and misunderstandings regarding Down syndrome.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In general, the self-determination abilities of people with intellectual disabilities are debatable (Etawi & Altarawneh, 2023). The belief exists that people with intellectual disabilities, including individuals with Down syndrome, cannot self-determine or make autonomous decisions; however, selfdetermination and decision-making skills can be inculcated in people with mental disabilities (AlTarawneh & Etawi, 2022;Mohaidat & Alkhtatbeh, 2021). A previously conducted study indicated that individuals with intellectual disabilities can imbibe a moderate degree of self-determination (Mohaidat & Alkhtatbeh, 2021).…”
Section: Self-determination Of People With Down Syndromementioning
confidence: 99%